"Shop floor recruitment - initiative to increase the factory manpower" of British American Tobacco Bangladesh - Haque, Fahmida (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.